Responsible Design of Smart Surveillance and Monitoring Systems (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2025)
Smart surveillance and monitoring systems -- AI-enhanced CCTV networks, behavioural analytics platforms, workplace monitoring tools, and biometric access control systems -- are increasingly deployed by public and private sector organisations that prioritise security and operational efficiency over the privacy, dignity, and autonomy implications for monitored individuals. Responsible design of these systems requires embedding ethical constraints at the architecture, algorithm, and governance levels -- not as retrospective compliance additions but as foundational design requirements. This paper proposes the Responsible Surveillance Design Framework (RSDF), a systematic methodology integrating privacy-by-architecture, proportionality assessment, purpose limitation enforcement, transparency design, and contestability mechanisms into a unified responsible design process for smart surveillance systems. RSDF is evaluated through application to five surveillance design cases: urban public space monitoring, workplace productivity surveillance, retail loss prevention AI, school safety monitoring, and hospital patient monitoring. The framework introduces the Responsible Design Score (RDS) integrating privacy protection strength, proportionality, transparency, and contestability. Key results: hospital patient monitoring achieves the highest RDS (0.784) due to clinical governance framework; workplace productivity surveillance achieves the lowest RDS (0.312) driven by consent invalidity and purpose creep; privacy-by-architecture is the single highest-impact design intervention across all five cases. The framework provides a responsible surveillance design checklist and process for deployers and regulators.